Application Of Autogenic Relaxation Therapy To Communities With High Blood Pressure In Sawah Lebar Urban Village, Ratu Agung Sub-District, Bengkulu City - Porgasari, Julisti; susiyanti , Leti; Oktavia , Nedisva; Agustami , Hesti Tri; Elfrida G , Kristauli; Sumarni , Ririn; Nuh, Yalta Hasanuddin; Sulastri, Sulastri (Universitas Dehasen Bengkulu, 2024)
Hypertension is an invisible killer that rarely causes symptoms. Increasing public awareness is key, as is access to early detection. Rising blood pressure is a serious warning sign that important lifestyle changes are urgently needed.One of the other factors that affect hypertension is a family history, biological parents have a history of hypertension then it will be a 45% chance of being passed on to their offspring, and if only one parent has hypertension then there is a 30% chance that it will be passed on to their offspringPatient knowledge and awareness about hypertension is an important factor in achieving blood pressure control. Knowledge about hypertension is a bad lifestyle habit that contributes to the occurrence of hypertension, If a person's weight increases, then the blood volume will also increase so that the burden of the heart in pumping blood also increases.Autogenic relaxation has its own uniqueness compared to other relaxations, namely it can have an effect on blood pressure and pulse frequency immediately after treatment.